If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -105 = 6x Reorder the terms: -105 + x = 6x Solving -105 + x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -105 + x + -6x = 6x + -6x Combine like terms: x + -6x = -5x -105 + -5x = 6x + -6x Combine like terms: 6x + -6x = 0 -105 + -5x = 0 Add '105' to each side of the equation. -105 + 105 + -5x = 0 + 105 Combine like terms: -105 + 105 = 0 0 + -5x = 0 + 105 -5x = 0 + 105 Combine like terms: 0 + 105 = 105 -5x = 105 Divide each side by '-5'. x = -21 Simplifying x = -21
| .33x+7=1 | | -18-8x=-10(x+4) | | f(x)=15x^4+8x^3-18x^2+1 | | m-1=-13+3m | | 3/103/4 | | 3(2x-5)+24-4x=9 | | 25x^2=-45x-18 | | 2/3(x-9)^-(1/3) | | -10-3a=a-6-3a | | x+x+55(x+38)=180 | | 25x^2+45x-18=0 | | 45=9-2b | | 4-4a=-3a+a | | 3k-2=4 | | .25x+3=-9 | | x=4x-0.1x^2 | | 11ln(9x)=12 | | 7+8r=7-4r | | x+x+43*x-32=180 | | 3(a-10)=42 | | -.5x+15=20 | | -2+5x=-3x+7x | | p+.12p=56 | | -5=a^2+3 | | t/3+t/2-350=270 | | 1-4v=15-6v | | 11+x=-33 | | http://media.apexlearning.com/Images/201305/30/25030d05-eb1d-46a7-bf10-8e6086df63c3.gif | | -12/6=X | | p+.12p=52 | | 5n+4n=8n-7 | | 4x+3y-4=7y+12 |